Rhetoric as Deliberation or Manipulation? About Aristotle's Rhetoric and its Misuse in Recent Literature. Issue 1 (1st April 2014) - Jörke, Dirk
Abstract In contrast to some recent articles, which try to bridge the gap between Aristotle's Rhetoric and contemporary concepts of deliberative democracy, it is argued that Aristotle in this work does not plead for a rational and unemotional way of political decision making. On the contrary, his Rhetoric should be read as a manual for strategically oriented actors if not for demagogues. The well-known tension between the more ethical and the political parts of Rhetoric can be resolved if a distinction is made between a form of rhetoric, which has its place in an ideal polis, and the kind of rhetoric that is necessary in a corrupt regime. For Aristotle the democratic regime of Athens is such a corrupt regime. In the last part of this paper, it is demonstrated that Aristotle in his Rhetoric highlights the non-cognitive and emotional features of deliberative procedures and thereby corrects one of the most serious shortcomings of the theory of deliberative democracy.